Sustainable food consumption behaviors of generations Y and Z: A comparison study - My Hanh Doan; Anna-Lena Drossel; Remmer Sassen (Cleaner and Responsible Consumption)
This study examines the differences in food consumption behaviors between generations Y and Z to support the strategy development for a generational transition towards sustainable food consumption. Empirical data for the study is collected through an online survey with the participation of 175 young people in Germany. The Young Consumers’ Sustainable Consumption Behaviors (YCSCB) scale by Fischer et al. (2017) is applied as a foundation for questionnaire development with necessary adaptation to the topic of the study. This analysis theoretically breaks down the sustainable food consumption behavior measurement into thematic sub-categories that reflect specific aspects of food consumption among young adults, including throwaway-, carnivore-, healthy-lifestyle, food awareness, and food cost saving. The findings show that generation Z has greater food cost savings than generation Y. Besides age, correlations between gender and sustainable parental household to sustainable food awareness and food cost savings were also found. In order to efficiently promote sustainable consumption ideology and habits to different generations, businesses and social policies should tailor marketing and education campaigns such as emphasizing food cost saving to generation Z, or highlighting health benefits to men. The methodology and measurement scale applied in this study could be replicated in different research settings across different population groups and contextual factors.